2012
DOI: 10.1016/j.virol.2012.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of a novel eleven amino acid insertion directly N-terminal to a tetrabasic cleavage site confers intracellular cleavage of an H7N7 influenza virus hemagglutinin

Abstract: A critical feature of highly pathogenic avian influenza viruses (H5N1 and H7N7) is the efficient intracellular cleavage of the hemagglutinin (HA) protein. H7N7 viruses also exist in equine species, and a unique feature of the equine H7N7 HA is the presence of an eleven amino acid insertion directly N-terminal to a tetrabasic cleavage site. Here, we show that three histidine residues within the unique insertion of the equine H7N7 HA are essential for intracellular cleavage. An asparagine residue within the inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Notably, MHV S contains what appears to be an insertion of a stretch of residues upstream of the cleavage site (table 3), which are clearly linked to fusion activity (Taguchi and Shimazaki, 2000). In this regard, there are also parallels with influenza virus, where peptide insertions upstream of the cleavage site/fusion peptide modulate the fusion activity of H7 influenza viruses (Hamilton et al, 2012; Perdue, 2008). In addition, work on influenza virus HA have shown that glycosylations can have profound effects on cleavage activation, as bulky sugar moieties can create steric hindrance around the cleavage site, restricting access for proteases (Kawaoka et al, 1984; Tse et al, 2014).…”
Section: Discussion: Spike (S) Cleavage Motifs As Coronavirus Cellmentioning
confidence: 99%
“…Notably, MHV S contains what appears to be an insertion of a stretch of residues upstream of the cleavage site (table 3), which are clearly linked to fusion activity (Taguchi and Shimazaki, 2000). In this regard, there are also parallels with influenza virus, where peptide insertions upstream of the cleavage site/fusion peptide modulate the fusion activity of H7 influenza viruses (Hamilton et al, 2012; Perdue, 2008). In addition, work on influenza virus HA have shown that glycosylations can have profound effects on cleavage activation, as bulky sugar moieties can create steric hindrance around the cleavage site, restricting access for proteases (Kawaoka et al, 1984; Tse et al, 2014).…”
Section: Discussion: Spike (S) Cleavage Motifs As Coronavirus Cellmentioning
confidence: 99%
“…173 However, the intracellular cleavage of the equine H7N7 lineage was found to be due to an 11 amino acid motif adjacent to the MBCS that, when inserted into an LPAI H7N3 virus, increased the pathogenicity of infection. 175 In contrast, the H3N8 equine lineage may have originated wholly from an avian IAV source, and these viruses have been shown to undergo frequent intersubtype and intrasubtype reassortments. [178][179][180] Interestingly, the H3N8 virus in equine hosts preferentially binds to avian-like α-2,3-SA, where the receptors are abundantly present in the upper respiratory tract of horses.…”
Section: Equine Iavmentioning
confidence: 99%
“…In addition to the polybasic cleavage site, HPAI H7 HAs contain a peptide insert upstream of the HA cleavage site to increase the accessibility of the cleavage site to proteases (22). In other situations (most notably with equine H7N7 viruses), the addition of 11 amino acids adjacent to the cleavage site allowed increased cleavage and fusion activation (34,35), presumably by repositioning and increasing accessibility of the cleavage site motif. The impact of these types of modifications for H9 influenza virus has not been evaluated.…”
mentioning
confidence: 99%